Natal Verde - 30 Anos de Postais de Jorge Paiva - Paulo Trincão (Outros Títulos, 2019)
Green Christmas - 30 years of Postcards by Jorge Paiva, book organized by the Exploratório - Centro Ciência Viva of Coimbra, in partnership with the Order of Biologists and Coimbra University Press, brings together the collection of Christmas postcards that Jorge Paiva, bologist and tireless activist in defense of biodiversity and the environment, has been publishing and distributing worldwide since 1990. "Enjoy the beauty of postcards, read carefully and learn from their messages." [José Matos] "His message reached many thousands of people, students, teachers, readers and made many feel that they could, like him, contribute to "saving the planet"". [Paulo Renato Trincão] "This edition is a very valid tool in the educational work and the collective deepening of civic awareness [...]". [Luís Simões da Silva] "Each postcard tells a story of biodiversity in a different way, but always with relevance and challenge, urging us to act." Helena Freitas